2012
DOI: 10.1063/1.3688918
|View full text |Cite
|
Sign up to set email alerts
|

Strong vortex pinning in FeSe0.5Te0.5 epitaxial thin film

Abstract: We report on the magnetic field and angular dependence of the critical current density of epitaxial FeTe0.5Se0.5 thin films. The films exhibit high critical current values and weak dependence on the applied magnetic field. The Jc is larger for field parallel to the c-axis, which is the opposite behavior of what expected from the critical field anisotropy. The analysis of the activation energy for vortex motion indicates that the single pinning regime holds up to 9 T, suggesting that correlated pinning centers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
24
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 21 publications
8
24
1
Order By: Relevance
“…2. Nonetheless, it is a clear indication to TAFF behavior together with many other measurements on Fe-based superconductors interpreted with the TAFF model [10][11][12][13][14]. TAFF fits over restricted resistance, temperature, and magnetic-field ranges with U small compared to T are often reported in the context of a SIT [15,16].…”
Section: Superconducting Phasesupporting
confidence: 53%
“…2. Nonetheless, it is a clear indication to TAFF behavior together with many other measurements on Fe-based superconductors interpreted with the TAFF model [10][11][12][13][14]. TAFF fits over restricted resistance, temperature, and magnetic-field ranges with U small compared to T are often reported in the context of a SIT [15,16].…”
Section: Superconducting Phasesupporting
confidence: 53%
“…c-axis peak) is visible for all magnetic fields, as displayed in the inset of figure 6(c). This peak is related to correlated defects confirmed by TEM acting as effective pinning centers parallel to the c-axis [11][12][13][14].…”
Section: Resultsmentioning
confidence: 66%
“…On the other hand, Imai et al showed that the superconducting properties are not well correlated to the lattice mismatch of the substrates but rather connected to the cell constants of the films [9,10]. Furthermore, films on SrTiO 3 show a peak in the angular dependence of J c for H || c [11][12][13]. Similar c-axis peaks in J c (θ) have been observed for films deposited on CaF 2 substrate [14].…”
Section: Introductionmentioning
confidence: 84%
“…No evidence of intrinsic pinning was observed in Ba122; however, enhancements in J c ( H//ab ) due to extended correlated planar defects were found16. Fe(Se,Te) films, despite their much lower T c , revealed a high J c 171819 with a low J c anisotropy1819 and surprisingly showed signs of intrinsic pinning below 8 K20. The intrinsic pinning properties of SmFeAs(O,F) and LaFeAs(O,F) single crystals were studied by Moll et al 21.…”
mentioning
confidence: 91%